Romance languages and linguistic theory 2017 selected papers from 'Going Romance' 31, Bucharest - Nicolae, Alexandru, 1986-; Dragomirescu, Adina, 1983- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2021)
"This volume contains a selection of 18 peer-reviewed papers presented at the 31st edition of Going Romance. Phenomena found in Romance languages (European Portuguese, French, Italian, Spanish, Romanian), in Romance dialects (Cosentino, Salentino, southern Calabrese, Neapolitan, and Trevigiano), and even in creoles with a Romance lexifier (Makista and Kristang) either benefit from in-depth analyses confined to one single variety, or are subjected to comparative analysis (dialect vs standard language, dialect vs different major language(s), cross-dialectal comparison, cross-Romance comparison, and even comparison of language families). Theoretical and experimental approaches complement one another, as do diachrony and synchrony. Individually and as a whole, these contributions show how the Romance languages contribute to a better understanding of issues which are relevant in the current linguistic landscape: acquisition, n-words, ellipsis phenomena, focus and polarity, ditransitive constructions, grammaticalization theory, differential object marking, language ecology, event structure, cyclicity, passives and many more"--